2010
DOI: 10.1186/1471-2334-10-177
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Mycobacterium tuberculosis genotypes circulating in Ndola, Zambia

Abstract: BackgroundTuberculosis (TB) is one of the major public health problems in Zambia. However, information about lineages of M. tuberculosis complex (MTBC) isolates useful for epidemiology investigations is unknown. In this study, we investigated the diversity of MTBC isolates from Ndola, a typical Zambian urbanized city with a documented high HIV prevalence.MethodsThis was part of a prospective cohort study in subjects with sputum smear-positive pulmonary TB. Spoligotyping was used to genotype the MTBC isolates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 29 publications
3
46
4
Order By: Relevance
“…Compared with other infectious diseases, however, for which 20% of the population may generate 80% of transmission, TB transmission appears relatively more homogeneous (53,54). Previous studies in areas with high TB incidence rates have shown a wide range of transmission rates (clustering rates), ranging from 37 to 72% in settings with TB incidence rates of over 200 cases per 100,000 inhabitants (55)(56)(57).…”
Section: Total 754mentioning
confidence: 99%
“…Compared with other infectious diseases, however, for which 20% of the population may generate 80% of transmission, TB transmission appears relatively more homogeneous (53,54). Previous studies in areas with high TB incidence rates have shown a wide range of transmission rates (clustering rates), ranging from 37 to 72% in settings with TB incidence rates of over 200 cases per 100,000 inhabitants (55)(56)(57).…”
Section: Total 754mentioning
confidence: 99%
“…Since the present report presents essentially MIRU-VNTR data, hereafter the focus will be on microevolution concerning this particular marker. Most often, studies on polyclonal and multiple strain infections were conducted in settings with high TB burden [2][3][4][5]. Nevertheless, they have also been observed in areas with moderate TB incidence [6].…”
Section: Introductionmentioning
confidence: 97%
“…MIRU-VNTR typing [8,9], widely applied in molecular epidemiologic studies, facilitates the detection of polyclonal infections as the presence of more than one strain in a sample is likely to lead to the detection of multiple alleles in a number of loci. Depending on the number of implicated loci, two distinct mechanisms are considered responsible for the presence of such multiple alleles; ''inpatient'' microevolution of the infecting clone in case of the detection of double alleles in a single locus as opposed to simultaneous infection with two distinct MTB strains when two or more loci are concerned [2][3][4]10]. Microevolution can of course affect any genotypic marker, for example, a strain may evolve by losing a spacer of the initial spoligotype profile.…”
Section: Introductionmentioning
confidence: 99%
“…Such information is valuable for the development of new tools for TB control (Gagneux and Small, 2007). Furthermore, apart from differentiating MTBC strains, MIRU-VNTR typing can easily identify mixed infections in patient isolates (Mulenga et al, 2010).…”
Section: Mycobacterial Interspersed Repetitive Unit Typing-variable Nmentioning
confidence: 99%
“…Some of the more popular MTBC typing methods being used globally include IS6110-based restriction fragment length polymorphism (RFLP) (Van Embden et al, 1993), PCR based methods such as spoligotyping (Kamerbeek et al, 1997), mycobacterial interspersed repetitive unitsvariable number of tandem repeats (MIRU-VNTR) (Frothingham et al, 1998), single -nucleotide polymorphisms (Gutacker et al, 2006) and largesequence polymorphism analysis (De Jong et al, 2009;Mulenga et al, 2010).…”
Section: Introductionmentioning
confidence: 99%